Mechanical Characterization of Carbon Fibres Recycled by Steam Thermolysis: A Statistical Approach. (20th May 2018) - Boulanghien, M.; R'Mili, M.; Bernhart, G.; Berthet, F.; Soudais, Y.
Abstract : The recent development of technologies for recycling carbon fibre reinforced plastics (CFRPs) leads to the need to evaluate the mechanical response of recycled carbon fibres. As these fibres are likely to be degraded during the recycling treatment, it is very important to determine their tensile residual properties so as to evaluate their ability as reinforcement for new composite materials. Carbon fibres reclaimed by a steam-thermal treatment applied to degrade the epoxy resin matrix of a CFRP are here analysed. Two conditions were chosen so as to reach two degradation efficiency levels of the steam thermolysis. Several carbon fibre samples were selected for mechanical testing carried out either on single filaments using single fibre tensile tests or on fibre tows using bundle tensile tests. It is shown that the single fibre tensile test leads to a wide variability of statistical parameters derived from the analysis. Bundle tensile tests results were able to indicate that fibre strength of recycled carbon fibre is similar to corresponding as-received carbon fibres thanks to a statistically relevant database. Wide number of tested filaments enabled indeed to obtain low scatters.